2018
DOI: 10.1111/jhn.12559
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary carbohydrate quality and the prevalence of obesity and hypertension

Abstract: These results suggest that the quality of carbohydrates consumed is associated with the risk of obesity and hypertension. However, the cross-sectional design does not preclude reverse causality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 37 publications
3
32
1
2
Order By: Relevance
“…In our study, total fat intake has increased, and there is a possibility that the proportion of saturated fat in total fat intake increased. Kim et al reported that dietary carbohydrate quality was associated with the prevalence of hypertension among Korean adults using data from the 5th KNHANES . More detailed data collection and subsequent analysis of dietary risk factors are necessary in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, total fat intake has increased, and there is a possibility that the proportion of saturated fat in total fat intake increased. Kim et al reported that dietary carbohydrate quality was associated with the prevalence of hypertension among Korean adults using data from the 5th KNHANES . More detailed data collection and subsequent analysis of dietary risk factors are necessary in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…However, excessive amounts of carbohydrates intake can give negative impact on people’s health, longevity, and sustainability [ 37 ]. Moreover, dietary carbohydrates quality measured by dietary glycemic index, glycemic load, dietary fibre, and whole grains may play a more important role in population health than that amount [ 38 , 39 , 40 ]. Therefore, the difference in types and quality of carbohydrates intake between income groups should be put emphasis on further studies.…”
Section: Discussionmentioning
confidence: 99%
“…After these exclusions, 277 complete datasets per person were used in the analysis to establish the relationship between CQI and obesity/overweight. The weighted daily dietary GIs were calculated using the suggested formula: Weighted GI=∑(carbohydrate content of food item (CHOi) × GIi/daily total food carbohydrate content; where CHOi is each food’s carbohydrate content, GIi is each food’s GI and GIi is the GI value for the food 15. The GL value was calculated for each participant by multiplying the carbohydrate content in grams obtained from the portion of food consumed by the corresponding GI of that food divided by 100.…”
Section: Methods and Subjectsmentioning
confidence: 99%
“…A previous study13 defined Carbohydrate Quality Index (CQI) by taking into account dietary fibre intake, GI, whole grains-to-total grains ratio and solid carbohydrate to total carbohydrates. The inverse association between CQI and obesity/overweight has been shown in one prospective study14 and in a cross-sectional study in adults 15. However, both of these studies assessed only general obesity based on body mass index (BMI) criteria.…”
Section: Introductionmentioning
confidence: 99%